Perubahan Tutupan Lahan TNKS di Kawasan Resort Kambang Nagari Pelangai Gadang Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan - Satrima, Ega Dira; Ahyuni, Ahyuni (MASALIQ, 2024)
Kambang TNKS Resort Area Nagari Pelangai Gadang Ranah Pesisir District, Pesisir Selatan Regency is a conservation area. This type of research uses the Mixed Method method. This research is a planned, systematic, structured and measurable effort that utilizes both quantitative and qualitative research methods. The on-screen digitization technique is the process of changing geographic features on a map. The digitization process is carried out by delineating lanes and lines, delimiting the edges of existing objects. Such as roads, rivers, land parcel boundaries, buildings. The most dominating land area in 2017 is forest covering 47052.74 ha or around 84.34% of the total area and the most dominating land area in 2021 is also forest covering 45487.56 ha or around 81.53% of the total area. There are two factors that influence the change of land into forest farming areas (KTH), namely the lineage of ancestors and the economy. The most dominating land area in 2017 is forest covering an area of 47052.74 ha or around 84.34% of the total area and the most dominating land area in 2021 is also forest covering an area sof 45487.56 ha or around 81.53% of the total area, the factors that influence land change into forest farming areas (KTH) are 2, namely ancestral lineage and economy.